Effects of Vitamin D Supplementation on Fatigue and Disease Activity in Systemic Lupus Erythematous - Jetender Maheshwari, Noreen Maqbool Bokhari, Muhammad Shahzad Hafeez, Hizbullah, Niaz Ahmed, Saeed Taj Din (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Fatigue and high disease activity are prevalent and debilitating features of systemic lupus erythematosus (SLE). Emerging evidence suggests that vitamin D deficiency is associated with worse disease outcomes in SLE, including increased fatigue and heightened immune activation. Objective: To evaluate the effects of vitamin D supplementation on fatigue levels and disease activity in patients with systemic lupus erythematosus. Methodology: This interventional study was conducted at Department of Medicine, Kutiyana Memon Hospital, Kharadar, Karachi during the period from July 2022 to June 2023, including 80 SLE patients with confirmed vitamin D deficiency. All participants received cholecalciferol supplementation for 12 weeks. Fatigue was assessed using the Fatigue Severity Scale (FSS) and disease activity was measured using the SLE Disease Activity Index (SLEDAI) at baseline and post-treatment. Results: Among 80 SLE patients with baseline vitamin D deficiency, supplementation for 12 weeks significantly increased serum vitamin D levels (from 17.2 ± 4.8 to 34.6 ± 6.2 ng/mL; p < 0.001). This was accompanied by marked reductions in fatigue (FSS score from 5.8 ± 0.6 to 3.9 ± 0.7; p < 0.001) and disease activity (SLEDAI score from 12.4 ± 3.1 to 8.6 ± 2.9; p < 0.001). Improvements were more pronounced in patients who achieved vitamin D sufficiency (≥30 ng/mL). Adverse events were minimal and self-limiting, with no serious complications reported. Conclusion: Vitamin D supplementation significantly reduced fatigue and disease activity in SLE patients, suggesting a potential adjunctive role in disease management. Keywords: Systemic lupus erythematosus, vitamin D, fatigue, SLEDAI, autoimmune disease, supplementation.